2014
DOI: 10.1128/jvi.02841-13
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peripheral Blood Mononuclear Cells by Dengue Virus Infection Depotentiates Balapiravir

Abstract: bIn a recent clinical trial, balapiravir, a prodrug of a cytidine analog (R1479), failed to achieve efficacy (reducing viremia after treatment) in dengue patients, although the plasma trough concentration of R1479 remained above the 50% effective concentration (EC 50 ). Here, we report experimental evidence to explain the discrepancy between the in vitro and in vivo results and its implication for drug development. R1479 lost its potency by 125-fold when balapiravir was used to treat primary human peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 19 publications
1
53
1
Order By: Relevance
“…In contrast to the cytidinebased balapiravir, the potency of an adenosine-based inhibitor of DENV (NITD008) was much less affected by pre-infection of DENV or cytokine treatment. These results demonstrate that viral infection in patient before treatment could significantly affect the prodrug conversion to its active form; such effect is nucleoside class-dependent (Chen et al, 2014). Similarly, HIV infection of PBMCs was also reported to affect both the nucleoside analog triphosphate conversion and the concentration of corresponding natural nucleoside triphosphate, leading to reduced compound efficacy (Gao et al, 1993;García-Lerma et al, 2011).…”
Section: Effect Of Cell Types and Viral Infection On Triphosphate Nucmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast to the cytidinebased balapiravir, the potency of an adenosine-based inhibitor of DENV (NITD008) was much less affected by pre-infection of DENV or cytokine treatment. These results demonstrate that viral infection in patient before treatment could significantly affect the prodrug conversion to its active form; such effect is nucleoside class-dependent (Chen et al, 2014). Similarly, HIV infection of PBMCs was also reported to affect both the nucleoside analog triphosphate conversion and the concentration of corresponding natural nucleoside triphosphate, leading to reduced compound efficacy (Gao et al, 1993;García-Lerma et al, 2011).…”
Section: Effect Of Cell Types and Viral Infection On Triphosphate Nucmentioning
confidence: 76%
“…In support of the latter point, we recently showed that DENV infection triggered PBMCs to generate cytokines which decreased their efficiency to convert balapiravir to its triphosphate form, resulting in decreased antiviral potency (Chen et al, 2014). In contrast to the cytidinebased balapiravir, the potency of an adenosine-based inhibitor of DENV (NITD008) was much less affected by pre-infection of DENV or cytokine treatment.…”
Section: Effect Of Cell Types and Viral Infection On Triphosphate Nucmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, these observations may have clinical implications. When patients receive therapy, DENV has already established its replication, triggering an immune response to produce IFN and other cytokines (41,42). If patients are treated with brequinar, its ability to augment IFNinduced ISRE activation should enhance the overall antiviral status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the current compound has provided an opportunity to answer two paramount questions for dengue therapeutics development: can an antiviral drug reduce viremia in dengue patients (infected with DENV-2 or -3), and, if so, will viremia reduction prevent patients from developing severe hemorrhagic fever and shock? Since compound 14a is not a prodrug and directly inhibits viral NS4B, it is expected to eliminate the complications of nucleoside inhibitors (which require host kinases to convert them to their triphosphate forms before being antiviral active), as evidenced by the efficacy failure of balapiravir in dengue patients (6,33).…”
Section: Discussionmentioning
confidence: 99%